Lipofilling as a method of reconstructive treatment of breast cancer patients (а review of literature) - R. V. Lyubota; N. F. Anikusko; A. S. Zotov; R. I. Vereshchako; I. I. Lyubota (Опухоли женской репродуктивной системы, 2015)
Lipofilling is one of the most promising directions in reconstructive surgery in patients with breast cancer (ВС). Although, the first transplantation of autologous adipose tissue was performed in the late nineteenth century, widely used techniques associated with the introduction of liposuction (1980s years), which greatly simplified the fence autologous adipose tissue for subsequent transplantation. In clinical studies were proved efficacy and safety lipofilling for reconstruction in patients with ВС. In this paper presents the current data on the efficacy and safety of lipofilling as the primary or secondary method of reconstructive treatment of patients with ВС.